Mass and lifetime measurements of bottom and charm baryons in $p\bar p$ collisions at $\sqrt{s}= 1.96 TeV - Collaboration, CDF; Aaltonen, T; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Appel, J; Arisawa, T; Artikov, A; Asaadi, J; et al. (2014)
We report on mass and lifetime measurements of several ground state charmed and bottom baryons, using a data sample corresponding to 9.6 $\textrm{fb}^{-1}$ from $p\bar p$ collisions at $\sqrt{s}=1.96$ TeV, and recorded with the Collider Detector at Fermilab. Baryon candidates are reconstructed from data collected with an online event selection designed for the collection of long-lifetime heavy-flavor decay products and a second event selection designed to collect $J/\psi \rightarrow \mu^+ \, \mu^-$ candidates. First evidence for the process $\Omega_b^- \rightarrow \Omega_c^0 \, \pi^-$ is presented with a significance of $3.3\sigma$. We measure the following baryon masses: \begin{eqnarray} M(\Xi_c^{0}) = 2470.85\pm0.24(stat)\pm0.55(syst) \, MeV/c^2, \nonumber M(\Xi_c^{+}) = 2468.00\pm0.18(stat)\pm0.51(syst) \, MeV/c^2, \nonumber \\ M(\Lambda_b) = 5620.15\pm0.31(stat)\pm0.47(syst) \, MeV/c^2, \nonumber \\ M(\Xi_b^-) = 5793.4\pm1.8(stat)\pm0.7(syst) \, MeV/c^2, \nonumber \\ M(\Xi_b^0) = 5788.7\pm4.3(stat)\pm1.4(syst) \, MeV/c^2, \, and \nonumber \\ M(\Omega_b^-) = 6047.5\pm3.8(stat)\pm0.6(syst) \, MeV/c^2. \nonumber \end{eqnarray} The isospin splitting of the $\Xi_b^{-,0}$ states is found to be $M(\Xi_b^-)-M(\Xi_b^0)=4.7\pm4.7(stat)\pm0.7(syst)$ MeV/$c^2$. The isospin splitting of the $\Xi_c^{0,+}$ states is found to be $M(\Xi_c^0)-M(\Xi_c^+)$ = $2.85\pm0.30(stat)\pm0.04(syst)$ MeV/$c^2$. The following lifetime measurements are made: \begin{eqnarray} \tau(\Lambda_b) = 1.565\pm0.035(stat)\pm0.020(syst) \, ps, \nonumber \\ \tau(\Xi_b^-) = 1.32\pm0.14(stat)\pm0.02(syst) \, ps, \nonumber \\ \tau(\Omega_b^-) = 1.66^{+0.53}_{-0.40}(stat)\pm0.02(syst) \, ps. \nonumber \end{eqnarray}